(3ChbGa GdfHi Udi Gddg Ydjg hSdes ((3CMeO QaYJ s)
(3ChdgG (B:s
(3ai HjGf ChbGa GdfHi Udi Gddg Ydjg hSde HGdESfGO Qhi Yf GHf eSYhO QVi Gddg Yfg Cf GdfHi Udi Gddg Ydjg hSde cGf jba Ydi SHYI YTQ ehVYkG eG JLGhRgG CHOkG s
(3BNQgG (B:s
(3ef CKHJ ai HSedI CdgGce de jKHJ gfG hef CKHJ gfG de jKHJ gfGc JeJ s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
Keywords: (3GdbQGAGJ hGdJLhjOs